Religious Moderation Through Aqidah And Akhlak Learning In Islamic Elementary School - Isti'anah, Sheifi Zahrotul; Husnah, Barizatul; Nadlir, Nadlir (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Religious moderation through learning aqidah morals at Madrasah Ibtidaiyah is an effort to form a young generation who has a balanced understanding of religion, is tolerant, and can interact with people across religions. In this research, researchers used a library study method which analyzed data in the form of text directly. Madrasah Ibtidaiyah, as a basic Islamic educational institution, has a key role in forming children's character and moderate understanding of religion. In the context of learning moral beliefs at Madrasah Ibtidaiyah, religious moderation is an important foundation for forming a young generation that is tolerant and capable of establishing harmonious relationships with various levels of society. By involving teachers, curriculum, and the school environment, Madrasah Ibtidaiyah can become an educational institution that promotes religious moderation effectively and plays an important role in building a more inclusive and harmonious society. Keywords: Religious Moderation, Islamic Religious Education